Processing and Characterization of Germanium‐Based Borate Bioglass for Biological Applications - Nitisha K. Achmelwar; Shrishail B. Sollapur; Yugesh A. Kharche; S. G. Gajbhiv; Devakant Baviskar; Harshal A. Chavan; A. Bhowmik; Balewgize A. Zeru (Engineering Reports, 2025)
ABSTRACT This research discovered how borate‐based germanium‐doped Bioglass was made using a microemulsion‐assisted sol–gel technique for possible use in biology. The created Bioglass showed good network structure and open spaces. FTIR spectroscopy proved the existence of important groups, showing that germanium was successfully mixed into the borate structure. Placing the Bioglass in a solution that mimics body fluids helped it form a layer of hydroxyapatite on its surface, as shown by FTIR, XRD, and FESEM tests, indicating it was very compatible with biological systems. Toxicity assessments validated the nontoxic nature of the material at concentrations below 2 mg/mL. Furthermore, the bioglass exhibited antimicrobial activity against Staphylococcus aureus, Klebsiella pneumoniae, and Pseudomonas aeruginosa, with minimum inhibitory concentrations of 5, 5, and 2.5 mg/mL, respectively, highlighting its suitability for biological applications. This study proposes further investigations into repeatability, scalability, and clinical compliance, which are warranted to facilitate the translation of these promising germanium‐doped borate bioglass materials for therapeutic and regenerative medicine applications.